TI_GERICHTE 35.2013.91 vom 24. März 2014 , Ricorso dichiarato tardivo. Nessun motivo valido per restituzione del termine ricorsuale - TI Tribunale d'appello (2014)
Ricorso dichiarato tardivo. Nessun motivo valido per restituzione del termine ricorsuale